2016
DOI: 10.3390/pathogens5010022
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Staphylococcus aureus Virulence Factors in Skin Infection and Their Potential as Vaccine Antigens

Abstract: Staphylococcus aureus (S. aureus) causes the vast majority of skin and soft tissue infections (SSTIs) in humans. S. aureus has become increasingly resistant to antibiotics and there is an urgent need for new strategies to tackle S. aureus infections. Vaccines offer a potential solution to this epidemic of antimicrobial resistance. However, the development of next generation efficacious anti-S. aureus vaccines necessitates a greater understanding of the protective immune response against S. aureus infection. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 108 publications
(189 reference statements)
0
74
0
1
Order By: Relevance
“…Similarly, during a murine skin abscess model, IL-22 expression was previously identified to be independent of gd + T cells (34), but it was shown to be protective through the activation of antimicrobial peptide production (38). Inhibition of either IL-17A or IL-22 alone resulted in significantly larger lesion size, providing further evidence that both IL-17A and IL-22 are necessary for local clearance of S. aureus during an S. aureus skin infection (38,39). Consistent with this, we observed a significant increase in the influx of gd + T cells to the site of infection in the absence of IL-10.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, during a murine skin abscess model, IL-22 expression was previously identified to be independent of gd + T cells (34), but it was shown to be protective through the activation of antimicrobial peptide production (38). Inhibition of either IL-17A or IL-22 alone resulted in significantly larger lesion size, providing further evidence that both IL-17A and IL-22 are necessary for local clearance of S. aureus during an S. aureus skin infection (38,39). Consistent with this, we observed a significant increase in the influx of gd + T cells to the site of infection in the absence of IL-10.…”
Section: Discussionmentioning
confidence: 90%
“…Keratinocytes recognize the presence of S. aureus using pattern recognition receptors. Toll-like receptor 2 (TLR-2) on keratinocytes recognizes pathogen-associated molecular patterns (PAMPs) including peptidoglycan and lipopeptides [30]. Abu-Humaidan et al [31] have recently found that persistent intracellular S. aureus surviving in epidermal keratinocytes promoted complement activation on the cell surface; this complement activation, in turn, initiated cellular responses that subsequently reduced the intracellular bacterial burden by an extracellular signal-regulated kinase-dependent mechanism.…”
Section: Skin Immune Systemmentioning
confidence: 99%
“…For example, despite worldwide efforts, a vaccine for the clinically important Staphylococcus aureus has not made it to the market, yet. Basic research showed the importance of Th1 and Th17 responses in defence against staphylococci [68,69]. While Th17 is prominent in S. aureus clearance from skin and respiratory infections, Th1 responses protect from systemic infection.…”
Section: Multiple Causes May Prevent the Efficacy Of Bacterial Vacmentioning
confidence: 99%